Thermodynamic Study on the Vortex Teeth of Electric Scroll Compressors Based on Gradient Tooth Height - Bin Yang; Annan Li; Mengli Yuan; Jinguo Wu; Feng Gao; Mengqi Ge (Applied Sciences, 2024)
Through the analysis of the adhesion between the tooth head and axial clearance leakage attributed to vortex tooth shape deformation, an innovative tooth shape design concept has been introduced entitled “progressive change tooth high vortex tooth”. This unique design includes a gradual change in tooth height and an elevated vortex tooth profile, using temperature-sensitive materials to enhance the resolution of temperature loading on the vortex disc. By refining the process of resolving the temperature loading on the vortex disc, the mean temperature function of the fluid domain along the wall of the vortex tooth is calculated, and a steady-state temperature distribution model for the solid domain of the vortex tooth is formulated. Subsequently, a finite element model for the high eddy current disc is constructed using Abaqus 2021 finite element software, which facilitates the calculation of stress–strain distribution within the high eddy current disc under both gas pressure and temperature field loads. The results show that, especially under conditions of low speed and low exhaust pressure, the temperature load mainly influences the maximum deformation and stress distribution of the vortex tooth. Specifically, under the influence of heat-solid coupling, the maximum deformation of the progressive change tooth high vortex tooth occurs in close proximity to the central compression cavity, reaching up to 13 microns. These results provide a crucial theoretical basis for the structural design and performance optimization of the compressor.